A provenance metadata model integrating ISO geospatial lineage and the OGC WPS: Conceptual model and implementation. Issue 5 (3rd July 2019) - Closa, Guillem; Masó, Joan; Zabala, Alaitz; Pesquer, Lluís; Pons, Xavier
Abstract: Nowadays, there are still some gaps in the description of provenance metadata. These gaps prevent the capture of comprehensive provenance, useful for reuse and reproducibility. In addition, the lack of automated tools for capturing provenance hinders the broad generation and compilation of provenance information. This work presents a provenance engine (PE) that captures and represents provenance information using a combination of the Web Processing Service (WPS) standard and the ISO 19115 geospatial lineage model. The PE, developed within the MiraMon GIS & RS software, automatically records detailed information about sources and processes. The PE also includes a metadata editor that shows a graphical representation of the provenance and allows users to complement provenance information by adding missing processes or deleting redundant process steps or sources, thus building a consistent geospatial workflow. One use case is presented to demonstrate the usefulness and effectiveness of the PE: the generation of a radiometric pseudo‐invariant areas bench for the Iberian Peninsula. This remote‐sensing use case shows how provenance can be automatically captured, also in a non‐sequential complex flow, and its essential role in the automation and replication tasks in work with very large amounts of geospatial data.